KEPENTINGAN KEBIJAKAN POLITIK LUAR NEGERI FREEDOM OF NAVIGATION AMERIKA SERIKAT TERHADAP SENGKETA DI KAWASAN LAUT CHINA SELATAN - Richardo, Muhammad Richie; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research describes about the intervention that America was made in a South China Sea conflict between China and Brunei, Malaysia Philippines, Taiwan and Vietnam in terms of territorial claims in South China Sea. The intervention that America made aims to achieve peace and security in the South China Sea from conflict and war.The research method applies qualitative descriptive method, realism perspective and Foreign Policy theory. The author collected data from books, encyclopedia, journal, mass media and website to analyze the form intervention of America in South China Sea with using Freedom of Navigation Operation (FONOPs) as a foreign policy in international border. And America’s interest to involve in that conflict. The conclusion of this research is America’s interest to getting involved and intervene the conflict is to secure an international sea lanes especially Asia-Pacific region and also to suppress Chinese’s influence in Southeast Asia. Key words: Freedom of Navigation, International Sea Lanes, Influence, Hegemony, USA, China, Phillipines, Brunei, Malaysia, Vietnam, Taiwan, International Law of the Sea, Claiming, Conflict.